Distinct and Dissociable EEG Networks Are Associated With Recovery of Cognitive Function Following Anesthesia-Induced Unconsciousness - Rokos, Alexander; Mišić, Bratislav; Berkun, Kathleen; Duclos, Catherine; Tarnal, Vijay; Janke, Ellen; Picton, Paul; Golmirzaie, Goodarz; Basner, Mathias; Avidan, Michael S.; Kelz, Max B.; Mashour, George A.; et al. (Frontiers in Human Neuroscience, 2021)
The temporal trajectories and neural mechanisms of recovery of cognitive function after a major perturbation of consciousness is of both clinical and neuroscientific interest. The purpose of the present study was to investigate network-level changes in functional brain connectivity associated with the recovery and return of six cognitive functions after general anesthesia. High-density electroencephalograms (EEG) were recorded from healthy volunteers undergoing a clinically relevant anesthesia protocol and age-matched healthy controls. A battery of cognitive tests was administered at baseline, upon recovery of consciousness (ROC), and at half-hour intervals up to three hours following ROC. EEG-derived networks were maximally perturbed upon ROC but returned to baseline 30-60 minutes following ROC, despite deficits in cognitive performance that persisted up to 3 hours following ROC. Additionally, we identified distinct and dissociable functional connectivity networks, across all frequency bands, associated with specific cognitive tests during recovery from anesthesia. The results highlight that the return of cognitive function after anesthetic-induced unconsciousness is task-specific, with unique behavioral and brain network trajectories of recovery.